2008
DOI: 10.1073/pnas.0804320105
|View full text |Cite|
|
Sign up to set email alerts
|

Fractalization drives crystalline states in a frustrated spin system

Abstract: We measure a sequence of quantum Hall-like plateaux at 1/q: 9 >= q >= 2 and p/q = 2/9 fractions in the magnetisation with increasing magnetic field in the geometrically frustrated spin system SrCu2(BO3)2. We find that the entire observed sequence of plateaux is reproduced by solving the Hofstadter problem on the system lattice when short-range repulsive interactions are included, thus providing a sterling demonstration of bosons confined by a magnetic and lattice potential mimicking fermions in the extreme qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
98
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 32 publications
11
98
2
Order By: Relevance
“…A famous example is the Shastry-Sutherland model (SSM) [2], which is believed to accurately capture the physics of the orthogonal-dimer antiferromagnet SrCu 2 (BO 3 ) 2 . A big effort has been invested in understanding the appearance of various magnetization plateaus observed in experiments [3][4][5][6][7][8][9][10][11][12][13]. Early on it was found that the SSM has almost localized triplet excitations [5,14] which suggests that each plateau corresponds to a particular crystal of localized triplets.…”
mentioning
confidence: 99%
“…A famous example is the Shastry-Sutherland model (SSM) [2], which is believed to accurately capture the physics of the orthogonal-dimer antiferromagnet SrCu 2 (BO 3 ) 2 . A big effort has been invested in understanding the appearance of various magnetization plateaus observed in experiments [3][4][5][6][7][8][9][10][11][12][13]. Early on it was found that the SSM has almost localized triplet excitations [5,14] which suggests that each plateau corresponds to a particular crystal of localized triplets.…”
mentioning
confidence: 99%
“…We also discuss implications of microphases for the related multiferroic compounds Ca 3 CoMnO 6 and Lu 2 MnCoO 6 . [3][4][5], the spin-driven "nematic" transition in pnictides [6][7][8][9], and dimensional reduction in BaCuSi 2 O 6 [10,11]. Ca 3 Co 2 O 6 is another example comprising a triangular lattice of FM Ising chains coupled by weak antiferromagnetic (AFM) exchanges.…”
mentioning
confidence: 99%
“…Our mean field solutions reveal a quasi-continuous temperature dependence of the SDW wavelength, implying the existence of metastable states that explain the very slow dynamics observed in Ca 3 Co 2 O 6 . We also discuss implications of microphases for the related multiferroic compounds Ca 3 CoMnO 6 and Lu 2 Introduction.-Geometric frustration, low-dimensionality, and quantum fluctuations can lead to exotic phase transitions and states of matter [1,2] such as the field-induced magnetization plateaus of SrCu 2 (BO 3 ) 2 [3][4][5], the spin-driven "nematic" transition in pnictides [6][7][8][9], and dimensional reduction in BaCuSi 2 O 6 [10,11]. Ca 3 Co 2 O 6 is another example comprising a triangular lattice of FM Ising chains coupled by weak antiferromagnetic (AFM) exchanges.…”
mentioning
confidence: 99%
“…Unlike the celebrated case of quantum spin-1/2 Cu 2+ ions in the insulating compound SrCu 2 (BO 3 ) 2 , which realizes the collective dimer singlet ground state predicted for the SSL [10,11], RB 4 has large classical f moments with magnetic interactions mediated by itinerant electrons. Despite this, just as SrCu 2 (BO 3 ) 2 exhibits a series of fractional magnetization plateaus as a function of the magnetic field H with M/M S = 1/q (q here is an integer from 2 to 9, M is the * lindaye@mit.edu magnetization, and M S is the saturation M) [11][12][13][14], RB 4 also shows magnetization plateaus of unusual structure [15][16][17][18]. A particularly interesting limit is the trivalent R = Er and Tm, where a strong Ising single-ion anisotropy exists such that the f -electron moments may be described within up/down twofold degrees of freedom locked perpendicular to the SSL plane and the plateau transitions arise from complex spin-flip processes [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%